Evaluating DNA Methylation in Random Fine Needle Aspirates from the Breast to Inform Cancer Risk - Kala Visvanathan; Ashley Cimino-Mathews; Mary Jo Fackler; Pritesh S. Karia; Christopher J. VandenBussche; Mikiaila Orellana; Betty May; Marissa J. White; Mehran Habibi; Julie Lange; David Euhus; Vered Stearns; et al. (Wiley, 2022)
Introduction. Critical regulatory genes are functionally silenced by DNA hypermethylation in breast cancer and premalignant lesions. The objective of this study was to examine whether DNA methylation assessed in random fine needle aspirates (rFNA) can be used to inform breast cancer risk. Methods. In 20 women with invasive breast cancer scheduled for surgery at Johns Hopkins Hospital, cumulative methylation status was assessed in a comprehensive manner. rFNA was performed on tumors, adjacent normal tissues, and all remaining quadrants. Pathology review was conducted on blocks from all excised tissue. The cumulative methylation index (CMI) for 12 genes was assessed by a highly sensitive QM-MSP assay in 280 aspirates and tissue from 11 incidental premalignant lesions. Mann-Whitney and Kruskal Wallis tests were used to compare median CMI by patient, location, and tumor characteristics. Results. The median age of participants was 49 years (interquartile range [IQR]: 44-58). DNA methylation was detectable at high levels in all tumor aspirates (median CMI = 252, IQR: 75-111). Methylation was zero or low in aspirates from adjacent tissue (median CMI = 11, IQR: 0-13), and other quadrants (median CMI = 2, IQR: 1-5). Nineteen incidental lesions were identified in 13 women (4 malignant and 15 premalignant). Median CMI levels were not significantly different in aspirates from quadrants (p=0.43) or adjacent tissue (p=0.93) in which 11 methylated incidental lesions were identified. Conclusions. The diagnostic accuracy of methylation based on rFNA alone to detect premalignant lesions or at-risk quadrants is poor and therefore should not be used to evaluate cancer risk. A more targeted approach needs to be evaluated.